Driven diffusion in nanoscaled materials - Albers, Tony; Bauer, Michael; Borczyskowski, Christian von; Gerlach, Frank; Heidernätsch, Mario; Kärger, Jörg; Kondrashova, Daria; Radons, Günter; Schubert, Sebastian; Shakhov, Alexander; et al. (Diffusion Fundamentals, 2015)
Mass transfer processes in which specific interactions with environments lead to complex diffusion patterns, such as the occurrence of transient sub-diffusive behaviors or of heterogeneous diffusion, were studied by means of two different experimental techniques, namely single-particle tracking operating with single molecules and nuclear magnetic resonance operating with large molecular ensembles. As an important point, the combined application of these techniques allowed for a deeper insight into the microscopic diffusion mechanism in such complex systems, including those with broken ergodicity. Particle tracking concentrated on the “Influence of substrate surface properties on heterogeneous diffusion of probe molecules in ultrathin liquid films”. The mobility of liquids at solid-liquid interfaces is influenced by substrate heterogeneities. Here we study the distribution of surface silanols on differently treated silicon wafers with thermal oxide by confocal florescence microscopy of adsorbed Rhodamine G molecules. We further investigate the influence of the substrate properties on probe molecule diffusion in ultrathin liquid TEHOS films by single molecule tracking. The results are compared to simulations of two-layer diffusion employing heterogeneous substrates. Nuclear magnetic resonance has been applied to study translational diffusion of small organic molecules in nanopores and of polymer globules in the presence of larger polymer species. In both cases, the experiments revealed the occurrence of normal diffusion on the time scale of NMR experiments from ten to hundreds of milliseconds. While single particle tracking revealed the identical diffusivities for the former case, thus experimentally confirming the validity of the ergodicity theorem for diffusion, the discrepancies were noted for the latter case. More complex behavior revealing non-ergodic behavior for propagation of solid-liquid interfaces in disordered nanopores has further been studied using nuclear magnetic resonance cryoporometry. A common basis for comparing and analyzing the experimental observables accessed by the two methods is the distribution of diffusivities, which provides the probability of observing a given diffusivity fluctuation along a trajectory or in an ensemble. An overview of its properties is given and the advantages in analyzing heterogeneous, anisotropic, or anomalous diffusion processes are elaborated.